Acute and Chronic Carbon Monoxide Toxicity from Tobacco Smoking. Issue 1 (31st October 2019) - Dorey, Alyrene; Scheerlinck, Pieter; Nguyen, Hoanvu; Albertson, Timothy
Abstract: Introduction: Carbon monoxide (CO) is produced from incomplete combustion of hydrocarbons and is a by-product of tobacco smoking. Chronic cigarette smokers often have carboxyhemoglobin (COHb) concentrations as high as 10%. We report a case of severely elevated COHb and polycythemia because of tobacco smoking and provide a review of the literature regarding elevated COHb in smokers. Materials and Methods: A comprehensive search of PubMed and Google Scholar was performed looking for articles on tobacco smoking and CO, COHb, CO poisoning, cigarettes, pipes, cigars and water pipes/hookah smokers. Result: COHb levels in frequent cigarette smokers generally range from 4.2% presmoking to 8.6% postsmoking. A heavy cigarette smoker presented twice with symptoms of CO toxicity and was found to have levels 21.8 to 24.2%. Cigar smokers have been found to have COHb ranging as high as 13.0 to 38.6% in case reports. Waterpipe or "hookah" smokers generally have COHb levels 10.1% +/−2.5% and case reports, and series of even higher levels associated with CO toxicity symptoms are common. Waterpipe smokers have been found to have COHb levels as high as 39.2% after smoking. Conclusions: Many active duty military and military veterans are tobacco smokers and these patients and their health care providers should be aware of the adverse effects of CO toxicity from tobacco smoking. Patients may have symptoms such as headaches, syncope, and ataxia in the setting of acute CO toxicity; however, the chronic effects of CO may not be completely understood. Future work could explore chronic CO toxicity and its effects on strength and exercise tolerance in military personnel and provide education to service members, veterans, and health care providers.